1997
DOI: 10.1095/biolreprod57.6.1312
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mitotic Cyclin B1 is not Confined to Proliferating Cells in the Rat Testis1

Abstract: Spermatogenesis is a precisely controlled and timed process comprising mitotic divisions of spermatogonia, meiotic divisions of spermatocytes, and the maturation and differentiation of haploid spermatids. Cell proliferation is controlled by genes involved in the regulation of the cell cycle. Among the principal regulatory proteins are cyclins, which are categorized according to their appearance during the cell cycle. B-type cyclins are mitotic cyclins and function at the G2/M transition of the cell cycle. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
4
24
3
Order By: Relevance
“…2). Our observation that some cell cycle genes are transcriptionally expressed at higher levels in purified round spermatids than in purified pachytene spermatocytes is consistent with previous reports (14). However, 18 of these genes were maximally expressed at stages XIII-XIV or stage I ( Table 3), indicating that their increased expression begins in spermatocytes.…”
Section: Analysis Of Defined Stages Of the Cycle Of The Seminiferous supporting
confidence: 92%
“…2). Our observation that some cell cycle genes are transcriptionally expressed at higher levels in purified round spermatids than in purified pachytene spermatocytes is consistent with previous reports (14). However, 18 of these genes were maximally expressed at stages XIII-XIV or stage I ( Table 3), indicating that their increased expression begins in spermatocytes.…”
Section: Analysis Of Defined Stages Of the Cycle Of The Seminiferous supporting
confidence: 92%
“…the cyclin B1 protein has been found to be expressed in postmeiotic spermatids and Sertoli cells but not in spermatogonia and spermatocytes (Gromoll et al, 1997), although no expression of cyclin B1 and B2 protein has been detected in the spermatids of mice testes (Brandeis et al, 1998). In medaka, a teleost fish, it has been reported that the cyclin B1 protein was expressed in spermatogonia and spermatocytes, except during the anaphase, whereas cyclin B2 was expressed in the same cells continuously (Mita et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of rats to 14 days of ANT treatment induces a quantitative reduction of germ cell production but spermatogenic stages can still be recognized (Chandolia et al 1991b, Brinkworth et al 1995, Gromoll et al 1997. When extrapolated for the average time needed by a spermatogonium to develop into a mature testicular sperm, the difference is 1·2 days.…”
Section: Discussionmentioning
confidence: 99%